Characterizing the spatiotemporal features of functional connectivity across the white matter and gray matter during the naturalistic condition - Hu, Peng; Wang, Pan; Zhao, Rong; Yang, Hang; Biswal, Bharat B. (Frontiers in Neuroscience, 2023)
The naturalistic stimuli due to its ease of operability has attracted many researchers in recent years.However, the influence of the naturalistic stimuli for whole-brain functions compared with the resting state is still unclear. In this study, we clustered gray matter (GM) and white matter (WM) masks both at the ROI-and network-levels. Functional connectivity (FC) and inter-subject functional connectivity (ISFC) were calculated in GM, WM, and between GM and WM under the movie-watching and the resting-state conditions. Furthermore, intra-class correlation coefficients (ICC) of FC and ISFC were estimated on different runs of fMRI data to denote the reliability of them during the two conditions. In addition, static and dynamic connectivity indices were calculated with Pearson correlation coefficient to demonstrate the associations between the moviewatching and the resting-state. As the results, we found that the movie-watching significantly affected FC in whole-brain compared with the resting-state, but ISFC did not show significant connectivity induced by the naturalistic condition. ICC of FC and ISFC was generally higher during movie-watching compared with the resting-state, demonstrating that naturalistic stimuli could promote the reliability of connectivity. The associations between static and dynamic ISFC were weakly negative correlations in the naturalistic stimuli while there is no correlation between them under resting-state condition. Our findings confirmed that compared to resting-state condition, the connectivity indices under the naturalistic stimuli were more reliable and stable to investigate the normal functional activities of the human brain, and might promote the applications of FC in the cerebral dysfunction in various mental disorders.